A comparative cost analysis study of pulmonary robotic and video-assisted lobectomy: results of a randomized controlled trial (BRAVO Study) - RICARDO MINGARINI TERRA; JULIANA ROCHA MOL TRINDADE; PEDRO HENRIQUE XAVIER NABUCO DE ARAUJO; LETICIA LEONE LAURICELLA; EVELISE PELEGRINELLI ZAIDAN; PAULO MANUEL PÊGO FERNANDESA (Revista do Colégio Brasileiro de Cirurgiões)
ABSTRACT Introduction: Robotic thoracic surgery has potential benefits, but the cost is still considered a limiting factor for its wide dissemination in most countries. Methods: We compared the costs of robotic-assisted (RATS) and video-assisted thoracic surgery (VATS) in the treatment of lung cancer or pulmonary metastasis. Cost analysis was based on micro-costing and individual cost analysis during surgical admission and frequency of services (emergency service, clinic visits, imaging exams, chemotherapy and radiotherapy, reoperation or additional procedures, rehospitalization, and ICU stay) during postoperative 90-day follow-up. Results: A total of 76 patients were included in this cost analysis (RATS=37, VATS=39). Groups were equivalent in terms of age, gender, comorbidities, and pre-operative status. Total costs of pulmonary lobectomy did not differ between the RATS and VATS groups when considering cost of surgical hospitalization and follow-up of up to 90 days. Mean individual cost per patient in the RATS group was R$35,590.41 (±12,514.97) and R$41,066.98 (±25,891.04) in the VATS group, p=0.564. Conclusion: Robotic and video-assisted thoracic surgery had similar costs, but longer follow-up studies could be important to demonstrate RATS and VATS costs differences.